Inflammatory Response and Renal Function Following Endovascular Repair of the Descending Thoracic Aorta. (April 2015) - Moulakakis, Konstantinos G.; Sfyroeras, George S.; Papapetrou, Anastasios; Antonopoulos, Constantine N.; Mantas, George; Kakisis, John; Alepaki, Maria; Mylonas, Spyridon N.; Karakitsos, Petros; Liapis, Christos D.
Purpose: To evaluate inflammatory response and renal function after thoracic endovascular aortic repair (TEVAR) of lesions in the descending thoracic aorta.Methods: Thirty-two consecutive patients treated with TEVAR from January 2010 to August 2013 were enrolled in this prospective study. Two were excluded owing to dissecting thoracic aortic aneurysm (TAA) extending into the renal arteries with renal failure in one and a saccular TAA in which a multilayer flow-modulating stent was implanted in the other. This left 30 patients (28 men; mean age 68.8±5.9 years) with 28 TAAs, an aortic dissection, and an aortic ulcer for the analysis. Temperature and serum levels of white blood cells (WBCs), C-reactive protein (CRP), interleukin-10 (IL-10), IL-6, IL-8, tumor necrosis factor-alpha (TNF-α), creatinine, urea, and cystatin C were measured preoperatively and at 24 and 48 hours postoperatively.Results: Statistically significant increases in temperature and serum levels of WBCs, CRP, IL-10, and IL-6 were observed 24 and 48 hours postoperatively compared to baseline (all p<0.05). The number of endografts and the coverage of the celiac or subclavian artery did not affect the magnitude of the inflammatory response. No significant differences were observed concerning serum levels of IL-8, TNF-α, creatinine, or cystatin C from baseline to 24 or 48 hours postoperatively.Conclusion: Endograft implantation in the thoracic aorta may propagate an inflammatory response during the early postoperative period. No clinical adverse events related to the increased inflammatory response were observed. Renal function does not seem to be deteriorated after TEVAR in the descending thoracic aorta.